Self-Assembly of Poly(g-benzyl L-glutamate)-block-poly(ethylene glycol) and Poly(g-benzyl L-glutamate)-graft-poly(ethylene glycol) Blend in Ethanol - Zhu, Guo-Quan; Wang, Fa-Gang; Li, Guo-Chang; Gao, Qiao-Chun; Liu, Yu-Ying (Asian Journal of Chemistry, 2013)
Poly(g-benzyl L-glutamate)-block-poly(ethylene glycol) (PBLG-block-PEG) and poly(g-benzyl L-glutamate)-graft-poly(ethylene glycol) (PBLG-graft-PEG) were synthesized by a standard N-carboxyl-g-benzyl-L-glutamate anhydride method and by an ester exchange reaction, respectively. The self-association behaviours of PBLG-block-PEG/PBLG-graft-PEG blend in ethanol were investigated by transmission electron microscopy and viscometry. It was showed that the polypeptide copolymer blend could self-assemble to form polymeric micelles with a core-shell structure in the shape of tree-like. Effects of the testing temperature and the weight ratio of PBLG-block-PEG to PBLG-graft-PEG on the critical micelle concentration of the polypeptide copolymer blend in ethanol were studied.